2006
DOI: 10.1529/biophysj.105.074856
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Bending of DNA by a Single TATA-Box Binding Protein

Abstract: The TATA-box binding protein (TBP) is required by all three eukaryotic RNA polymerases for the initiation of transcription from most promoters. TBP recognizes, binds to, and bends promoter sequences called "TATA-boxes" in the DNA. We present results from the study of individual Saccharomyces cerevisiae TBPs interacting with single DNA molecules containing a TATA-box. Using video microscopy, we observed the Brownian motion of beads tethered by short surface-bound DNA. When TBP binds to and bends the DNA, the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…The excursions of the bead were analyzed by a principal component analysis as detailed in ref. 25 and in SI Text. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excursions of the bead were analyzed by a principal component analysis as detailed in ref. 25 and in SI Text. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the literature (25,27) and the results from Fig. S3, we imposed the following selection criteria to minimize the occurrence of unspecific tethers in the analyzed datasets: (i) Results from beads that probably were attached directly to the surface, or by unspecific tethers, and hence had a small RMSD were discarded, and (ii) if the positions visited by the bead displayed a low degree of symmetry (s) as defined in SI Text, the bead might be attached to the surface by more than one DNA tether and the time series was discarded.…”
Section: Resultsmentioning
confidence: 99%
“…5). The calculation of the scattering amplitudes has been slightly modified from its application of analyzing Brownian motion of DNAtethered beads (Tolic-Norrelykke et al, 2006). For a twodimensional image, the tensor of inertia I is given by the following matrix ͒ / 2 (standard deviation around the center of mass) for the individual channels as well as the ratio S = S red / S green .…”
Section: Appendix: Quantitative Image Analysismentioning
confidence: 99%
“…Despite the high sequence identity and structural conservation of TBP in the archaeal-eukaryotic lineage we found that TBP from the euryarchaeal organism M. jannaschii (Mj) and from the crenarchaeal organism Sulfolobus acidocaldarius (Sa) do not follow a common DNA bending mechanisms and deviate significantly from the bending pathway observed for the eukaryotic TBP-TF(II)B-DNA interaction [12,78,79]. Interestingly, unlike all other TBP-DNA-promoter DNA interactions described so far, TBP from S. acidocaldarius was not able to induce DNA bending by itself but strictly required TFB to evoke the conformational change in the DNA.…”
Section: Early Steps Of Initiationmentioning
confidence: 99%